2024
DOI: 10.1093/ofid/ofae102
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Immunologic Antiviral Therapy With Omalizumab (CIAO)—a Randomized Controlled Clinical Trial

Michelle Le,
Lauren Khoury,
Yang Lu
et al.

Abstract: Background Omalizumab is an anti-IgE monoclonal antibody used to treat moderate to severe chronic idiopathic urticaria, asthma and nasal polyps. Recent research suggested that omalizumab may enhance the innate antiviral response and have anti-inflammatory properties. Objective We aimed to investigate the efficacy and safety of omalizumab in adults hospitalized for COVID-19 pneumonia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This randomized, double-blind, controlled phase II trial showed that omalizumab may be effective in reducing progression to mechanical ventilation or death at day 14 and also useful for reducing all-cause mortality on day 28. This study also provides the first clinical evidence for a possible antiviral and/or anti-inflammatory effect of omalizumab in non-atopic patients hospitalized for a severe viral respiratory disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This randomized, double-blind, controlled phase II trial showed that omalizumab may be effective in reducing progression to mechanical ventilation or death at day 14 and also useful for reducing all-cause mortality on day 28. This study also provides the first clinical evidence for a possible antiviral and/or anti-inflammatory effect of omalizumab in non-atopic patients hospitalized for a severe viral respiratory disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%